2021
DOI: 10.21203/rs.3.rs-923368/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Individual citizens' resilience to disasters caused by floods: a case study of Belgrade

Abstract: Due to the increasing frequency and variety of disasters caused by floods and their effect on people, environment, material, and cultural goods, there is an unavoidable need to improve the security of citizens through innovative solutions to improve Serbian citizens' resilience to such disasters. The subject of the research is a comprehensive examination of the levels and factors that affect the level of individual resilience of the citizens of Belgrade to the consequences of disasters caused by floods. By app… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Furthermore, an analysis of the literature reveals that numerous studies have investigated the effects of disaster risk reduction education programs on students' knowledge, attitudes, and behaviors concerning disaster preparedness and response [83][84][85][86][87][88][89][90][91][92]. These programs often include curriculum integration, training workshops, simulation exercises, and community engagement strategies [2,4,12,15,27,30,42,45,48,52,55,57,90,[93][94][95][96][97][98][99][100][101]. Additionally, there are numerous studies assessing the safety and resilience of school infrastructure and facilities to mitigate risks and ensure the well-being of students and staff during disasters [16,29,81,96,97,99,[102][103][104][105][106][107][108].…”
Section: Literature Review On School-based Disaster Risk Reduction An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an analysis of the literature reveals that numerous studies have investigated the effects of disaster risk reduction education programs on students' knowledge, attitudes, and behaviors concerning disaster preparedness and response [83][84][85][86][87][88][89][90][91][92]. These programs often include curriculum integration, training workshops, simulation exercises, and community engagement strategies [2,4,12,15,27,30,42,45,48,52,55,57,90,[93][94][95][96][97][98][99][100][101]. Additionally, there are numerous studies assessing the safety and resilience of school infrastructure and facilities to mitigate risks and ensure the well-being of students and staff during disasters [16,29,81,96,97,99,[102][103][104][105][106][107][108].…”
Section: Literature Review On School-based Disaster Risk Reduction An...mentioning
confidence: 99%
“…However, in reality, education is sporadic and varies from school to school [44]. It involves different entities and forces of protection and rescue, such as the police and firefighting rescue units [45]. Those citizens who don't receive education in disaster risk reduction and emergency management during their primary and secondary education can acquire basic knowledge through the activities of entities specializing in protection and rescue, as dictated by specific laws and program activities [46].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Foster (2007) provides an additional framework, characterizing regional resilience as the area's capacity to anticipate, anticipate, and effectively respond to disruptions as well as recover from them. Resilience, for instance, might entail having the capacity to endure and adjust to unforeseen circumstances (Cvetković, Bošković, & Ocal, 2021;Hochrainer-Stigler et al, 2021). This may include people's capacity to bounce back from hardship or trauma swiftly and take decisive action to get beyond obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…Community disaster resilience (CDR) has become an important social goal that attracts the attention of scientists and decision-makers in various sectors and scientific disciplines (Aleksandrina, Budiarti, Yu, Pasha, & Shaw, 2019;Cvetković, Bošković, & Ocal, 2021;Cvetković & Filipović, 2018;Dufty, 2012;Goyal, 2019;Jehoshaphat & Oghenah, 2021;Jurgens & Helsloot, 2018;Kabir, Hossain, & Haque, 2022;Keck & Sakdapolrak, 2013;Liu & Mishna, 2014). The analysis of the literature on CDR (Aitsi-Selmi, Egawa, Sasaki, Wannous, & Murray, 2015;Akter, Roy, & Aktar, 2023;Aleksandar, Cvetković, & Sudar, 2016;Baruh, Dey, & Dutta, 2023;El-Mougher, Abu Sharekh, Abu Ali, & Zuhud, 2023;Mohammed Mohammed El-Mougher, Sharekh, Ali, & Zuhud, 2023;Fujioka, 2016;Holmes, 2016;Jurgens & Helsloot, 2018;Kabir et al, 2022;Liu & Mishna, 2014;Winderl, 2014) and social identity (SI) has identified a number of shortcomings (Figure 1) that need to be addressed, which indicate significant importance of the projected research: insufficiently examined the impact of SI on building CDR; there is no consensus on the content and scope of the concept of resilience, on the unique dimensions and indicators of CDR and SI; there are no clearly defined measures and scales of CDR and SI; development of tools to measure CDR are at the emerging stage insufficiently developed, undeveloped generic framework of CDR that could be applied to different social communities; insufficiently developed procedures for designing and validating tools for measuring CDR; insufficiently examined influences systematized indicators of SI on building CDR; some CDR frameworks have been developed specific to a particular disaster and some other for a specific geographical area; insufficiently developed strategies, recommendations and programs for improving the level of CDR; insufficiently developed and elaborated predictive models of the impact of different variables on the further development of CDR; insufficiently investigated influences of SI (cognitive, evolutionary and emotional dimensions) on strengthening or weakening CDR; the lack of a methodology to engage and empower resil...…”
Section: Introductionmentioning
confidence: 99%